2022
DOI: 10.1152/advan.00173.2020
|View full text |Cite
|
Sign up to set email alerts
|

A task-based learning strategy in preclinical medical education

Abstract: Preclinical Task based learning (TskBL) is a simulated learning approach in which focus for students is a real task done by a medical professional. TskBL includes standardized patient encounters and is helpful to provide Early Clinical Exposure. Our study aimed at planning, implementing and assessing TskBL among first year Medical students and comparing it to conventional method of tutorials in Physiology MBBS curriculum.This is a non-equivalent group quasi experimental study approved by Institutional ethics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[ 22 ] Shenoy R et al . [ 23 ] recently published a simulated form of pre-clinical task-based learning (TskBL) and compared it to conventional tutorials in first-year undergraduate medical school in physiology. They found that the students performed better [assessment scores in multiple-choice questions (MCQs) and Objective Structured Clinical Examination (OSCE)] in a simulation-based group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Shenoy R et al . [ 23 ] recently published a simulated form of pre-clinical task-based learning (TskBL) and compared it to conventional tutorials in first-year undergraduate medical school in physiology. They found that the students performed better [assessment scores in multiple-choice questions (MCQs) and Objective Structured Clinical Examination (OSCE)] in a simulation-based group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It allows students to have access to the information in the moment that they need to learn with the help of technology [5] and improves their levels of cognition and skills [23,24]. These advantages can be useful in clinical education, where there is patient load [15] and students need to have access to relevant and concise information while managing patients. There are some studies that have assessed the effect of ML in medical education, though a few have assessed students' clinical performance in a real work setting, and most of them have evaluated students' reaction and knowledge acquisition [5].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, TBL supports the integration of medical knowledge with patient care, i.e., amalgamation of the theory and practice [13]. It is shown that TBL is an effective clinical teaching strategy for both undergraduate [14,15] and post graduate [16] medical education. However, there are some potential limitations for implementing TBL in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Frerejean et al (2021), the results indicated that task-centered instructional design models, such as the four-component model, led to a rich knowledge base, and created harmony between performance and learning through the combination of learning in the educational environment and learning in the work environment (Frerejean et al, 2021). Other studies also show that task-centered learning has increased the level of knowledge and skills and improved the attitude toward the learning environment (Frerejean et al, 2021;Maggio et al, 2015;Rosenberg-Kima, 2012;Shenoy et al, 2022). The results of a study conducted by Costa et al (2022), suggest that the use of educational programs developed with 4C/ID has a high impact on performance, regardless of the academic area, the design of the study, and the outcome.…”
Section: Introductionmentioning
confidence: 99%